Increasing the Competency of Guidance and Counseling Teachers Through Preparing Basic Service Materials with the Assistance of Artificial Intelligence - Khadijah Lubis; Sigit Dwi Sucipto; Fadhlina Rozzaqyah; Yola Eka Putri; Resti Okta Sari; Amanda Putri Septriani; Nia Bening Mutiara (International Journal of Public Devotion, 2026)
The rapid development of digital technology requires guidance and counseling (BK) teachers to enhance their competencies and adapt to technological advancements, particularly in designing engaging and contextual service materials. This community service program aimed to improve the professional competence of BK teachers through the utilization of Artificial Intelligence (AI), specifically ChatGPT, as a tool for developing basic guidance service materials. The activity was conducted from October 22 to 25, 2025, at SMA Negeri Sumatera Selatan, involving 23 BK teachers from 20 schools in Palembang City. The implementation methods included workshops, hands-on training, mentoring, and evaluation through pretest and posttest. The results revealed an increase in participants’ average scores from 112.17 to 139.57, with an N-Gain score of 0.72 (high category). These findings indicate that AI-based training effectively enhanced teachers’ understanding and skills in developing creative and relevant basic service materials. Supporting factors included participants’ enthusiasm and institutional support from the Palembang BK Teachers Association (MGBK), while challenges such as late attendance and technical difficulties during the pretest were successfully addressed by the organizing team. Overall, this program contributed to strengthening digital literacy and professional competence among BK teachers in facing educational transformation in the era of artificial intelligence.Peningkatan Kompetensi Guru BK Melalui Penyusunan Materi Layanan Dasar Berbantuan Artificial IntelligenceABSTRAKPerkembangan teknologi digital mendorong perlunya peningkatan kompetensi guru bimbingan dan konseling (BK) agar mampu beradaptasi dengan kemajuan teknologi, khususnya dalam penyusunan materi layanan yang menarik dan kontekstual. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi guru BK dalam memanfaatkan teknologi Artificial Intelligence (AI) berbasis ChatGPT sebagai alat bantu penyusunan materi layanan dasar. Kegiatan dilaksanakan pada 22–25 Oktober 2025 di SMA Negeri Sumatera Selatan, diikuti oleh 23 guru BK dari 20 sekolah di Kota Palembang. Metode pelaksanaan meliputi pelatihan (workshop), praktik langsung (hands-on training), pendampingan, serta evaluasi berbasis pretest dan posttest. Hasil kegiatan menunjukkan adanya peningkatan rata-rata skor peserta dari 112,17 menjadi 139,57, dengan nilai N-Gain sebesar 0,72 (kategori tinggi). Temuan ini menunjukkan bahwa pelatihan pemanfaatan AI efektif dalam meningkatkan pemahaman dan keterampilan guru BK dalam menyusun materi layanan dasar yang kreatif dan relevan. Faktor pendukung keberhasilan meliputi antusiasme peserta dan dukungan kelembagaan dari MGBK Kota Palembang, Secara keseluruhan, kegiatan ini berkontribusi terhadap peningkatan literasi digital dan profesionalisme guru BK dalam menghadapi transformasi pendidikan di era digital saat ini.Kata Kunci :guru BK; kecerdasan buatan; ChatGPT, layanan dasar